Effectiveness of task-oriented circuit training on the motor performance of ischaemic stroke patients: a study protocol for randomised clinical trial - Mohammad Anwar Hossain; Harun Or Rashid; Farzana Sharmin; Abid Hasan Khan; Farjana Sharmin; Md Forhad Hossain; Mahdi Ul Bari; Md Ershad Ali; Arnob Datta; Saiba Muhammad Sabrin; Md Rezaul Karim (BMJ Open Sport & Exercise Medicine)
Stroke is one of the most common causes of disability and death worldwide. With the rapidly growing stroke survivor population, it is crucial to identify an effective method for their healthcare. Recovery from stroke is followed by physiotherapy to promote rehabilitation. Task-oriented circuit training is designed to improve stroke patients’ overall functioning during rehabilitation. This research aims to assess the effectiveness of task-oriented circuit training compared with conventional physiotherapy. The investigators have planned an 8-week parallel, two-arm, prospective, randomised clinical study. Participants will be enrolled from eight branches of the centre for the rehabilitation of the paralysed (CRP). We have planned to recruit 506 stroke survivors via a 1:1 random assignment procedure for 24 months. As a main objective, the Action Arm Research Test and the Timed Up and Go will be used to test upper and lower limb motor function. The secondary objectives will include daily living and balance activities, which will be evaluated using the Barthel Index and the Berg Balance Scale. The post-test and follow-up data will be collected after 8 and 12 weeks. The final analysis will include dropouts and treatment side effects. This study has been granted ethical approval by the Ethics Review Committee of the CRP (CRP-R&E-0401-357)). All activities and interventions will be carried out following the Helsinki Declaration of 2020. The findings will be published in peer-reviewed journals and disseminated at international conferences. Trial registration number: CTRI/2023/09/057907 (21 September 2023) (Prospectively registered).